2022
DOI: 10.1038/s41598-022-06420-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA diversity of the Sardinian local cattle stock

Abstract: The aim of this research was to characterize the genetic diversity of the Sarda (Sa, n = 131), Sardo Bruna (SB, n = 44) and Sardo Modicana (SM, n = 26) cattle breeds, reared in the island of Sardinia (Italy). A portion of the mitochondrial DNA hypervariable region was sequenced, in order to identify a potential signature of African introgression. The FST coefficients among populations ranged between 0.056 for Sa vs SB and 0.167 for SB vs SM. AMOVA analysis indicated there was a significant differentiation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…All the15 sequences of five cattle breeds were categorised into 15 different haplotypes with haplotype diversity (HD) of 1.0 indicating high degree of haplotype diversity. Haplotype diversity of the present study was more than that reported by Chung (2013) in Korean cattle (0.052 to 0.20) and Petretto et al (2022) in Sardinian local cattle stock (0.879). The genetic differences were observed between populations of the same breed, indicating that the identified haplotypes may be used to characterize group specificities of each cattle breed (bulls, moderate yielders, low yielders).…”
Section: Genetic Structure Of Indigenous Cattle Breedscontrasting
confidence: 67%
“…All the15 sequences of five cattle breeds were categorised into 15 different haplotypes with haplotype diversity (HD) of 1.0 indicating high degree of haplotype diversity. Haplotype diversity of the present study was more than that reported by Chung (2013) in Korean cattle (0.052 to 0.20) and Petretto et al (2022) in Sardinian local cattle stock (0.879). The genetic differences were observed between populations of the same breed, indicating that the identified haplotypes may be used to characterize group specificities of each cattle breed (bulls, moderate yielders, low yielders).…”
Section: Genetic Structure Of Indigenous Cattle Breedscontrasting
confidence: 67%
“…Bovine mitochondrial DNA (mtDNA) has been widely used to evaluate the origin, phylogeny, genetic diversity, and population structure of this species as it has the characteristics of maternal inheritance, lack of recombination events, and high mutation rate [3][4][5]. Previously, the Cytb gene and the D-loop region of mitochondrial DNA (mtDNA) have been studied to assess the genetic diversity and phylogenetic performance of Guizhou Yellow cattle [6,7].…”
Section: Introductionmentioning
confidence: 99%